An Interpretive Phenomenological Inquiry of Family and Friend Reactions to Suicide Disclosure. (2nd July 2016) - Frey, Laura M.; Hans, Jason D.; Cerel, Julie
Abstract : Suicide attempt survivors' interpretations of reactions to attempts are understudied, yet could inform prevention efforts concerning subsequent attempts. Interviews with 40 attempt survivors about family and friend reactions were analyzed using interpretive phenomenological techniques. Three distinct patterns emerged as follows: (a) Stigmatizing statements and emphasis on reactor's feelings were interpreted as signs that attempt survivors were a burden to others, (b) avoidant reactions and excessive monitoring were interpreted as cues that suicidal behavior must remain hidden to not be a burden, and (c) asking questions and projecting strength were interpreted as signs that attempt survivors belonged and were not a burden. These findings highlight the importance of working with family and friends to encourage reactions that reduce the risk of future attempts.